Potyczki teorii i zdrowego rozsądku. Antoine Compagnon, Demon teorii. Literatura a zdrowy rozsądek, przeł. T. Stróżyński, Gdańsk 2010, wyd. słowo/obraz terytoria, 276 [3] ss. - Morawiec, Arkadiusz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The review concerns the Polish edition of the book Le démon de la theorie. Littérature et sens by Antoine Compagnon. The book contains a critical analysis of seven central questions of the theory of literature: literariness, the author (intention), the world (representation), the reader, style, history and value.